Increased Transglutaminase 2 Expression and Activity in Rodent Models of Obesity/Metabolic Syndrome and Aging - Penumatsa, Krishna C.; Falcão-Pires, Ines; Leite, Sara; Leite-Moreira, Adelino; Bhedi, Chinmayee D.; Nasirova, Sabina; Ma, Jing; Sutliff, Roy L.; Fanburg, Barry L. (Frontiers in Physiology, 2020)
Diastolic dysfunction of the heart and decreased compliance of the vasculature and lungs (i.e. increased organ tissue stiffness) are known features of obesity and the metabolic syndrome. Similarly, cardiac diastolic dysfunction is associated with aging. Elevation of the enzyme transglutaminase 2 (TG2) leads to protein cross-linking and enhanced collagen synthesis and participates as a candidate pathway for development of tissue stiffness. With these observations in mind we hypothesized that TG2 may be elevated in tissues of a rat model of obesity/metabolic syndrome (the ZSF 1 rat) and a mouse model of aging, i.e., the senescent SAMP8 mouse. In the experiments reported here, TG2 expression and activity were found for the first time to be spontaneously elevated in organs from both the ZSF1 rat and the SAMP8 mouse. These observations are consistent with a hypothesis that a TG2-related pathway may participate in the known tissue stiffness associated with cardiac diastolic dysfunction in these two rodent models. The potential TG2 pathway needs better correlation with physiologic dysfunction and may eventually provide novel therapeutic insights to improve tissue compliance.